Impact of Maternal Anxiety on Breastfeeding Practices - Freda D. Intiful; Louisa N. Nakotey; Nortey Eunice; Patricia M. Amos; Laurene Boateng (Mental Health Science)
ABSTRACT This study explored the relationship between maternal anxiety and breastfeeding practices among mothers in the Greater Accra Metropolis, Ghana, addressing a research gap in low‐ and middle‐income countries. A descriptive cross‐sectional design was used to recruit 161 breastfeeding mothers aged 18–45 years with babies aged 1–24 months from postnatal welfare clinics through convenience sampling. Data collection involved face‐to‐face interviews using a structured questionnaire that assessed sociodemographic information, maternal anxiety, and breastfeeding practices. Maternal anxiety was evaluated with the modified 12‐item Postpartum‐Specific Anxiety Scale (PSAS), covering four domains: maternal competence and attachment, infant safety and welfare, practical infant care, and psychosocial adjustment to motherhood. Breastfeeding practices were assessed according to World Health Organization guidelines. The study found a high prevalence of maternal anxiety, with 88.8% of mothers experiencing mild to moderate anxiety and 11.2% reporting severe anxiety, particularly in domains related to infant safety and psychosocial adjustments. Breastfeeding practices varied with 81% of infants still being breastfed at the time of the interview, 76% of mothers initiating breastfeeding within the first hour postpartum, and 73% practicing exclusive breastfeeding. Statistical analyses, including Wilcoxon tests, revealed significant associations between elevated anxiety related to maternal competencies and delayed breastfeeding initiation (p = 0.04). Maternal anxiety related to infant safety and care was significantly correlated with exclusive breastfeeding practices (p = 0.013 and p = 0.030). These findings highlight the need for tailored interventions to address maternal anxiety during the perinatal period to promote optimal breastfeeding practices and improve maternal‐infant health outcomes. Routine screening for anxiety and comprehensive support from healthcare providers are crucial, especially in resource‐constrained settings. Future research should explore the long‐term impacts of maternal anxiety on breastfeeding and child development across diverse socio‐cultural contexts.